Public-private partnership as a solution for integrating genetic services into health care of countries with low and middle incomes. - Meier, Florian; Schöffski, Oliver; Schmidtke, Jörg (Journal of community genetics, 2013)
In recent years scientific progress has dramatically raised the potential of genetic services, but the actual benefits of these developments are not universally shared. In countries of low and middle incomes, improvements in genetic services frequently lag behind. Since this is generally caused by lack of resources and not by the lack of political will, the question arises, how can one most easily acquire the necessary capital to improve the health care in these areas. Public-private partnerships (PPPs) offer one approach to solve this issue, aiming at the inclusion of private enterprises in the realisation of public authority services. So far PPPs have been used exclusively in other health service areas. In this paper a first attempt is being made to discuss the feasibility of transferring the concept of PPP to genetic services, and consideration is given as to where the most promising starting point might be. We start by defining a multilevel structure that needs to be considered in providing comprehensive genetic care. We continue by explaining the concept of PPPs and their current types of implementation in medical services. We then examine how the PPP model could be applied to genetic services or sections thereof. We arrive at the conclusion that a likely starting point for PPP in genetic services is at the level of the infrastructure building service.